Alteration of Spatial Pollution Compounds to Eutrophication Phenomenon of Small-Scale Area under Corona Virus Disease Circumstances - CHETIA, Rashmi; SAWASDEE, Vanatpornratt; POPRADIT, Ananya; HASIN, Sasitorn (Journal of Environmental Management and Tourism; Vol 12 No 3 (2021): JEMT Volume XII Issue 3(51) Summer 2021, 2021)
This research aims to study the alteration of spatial pollution compounds to the eutrophication phenomenon in water resources during the COVID-19 situation. Sixteen water resources were monitored to examine the impact of spatial pollution compound on eutrophication phenomenon discovered from the activities of the Valaya Alongkorn Rajabhat University under the Royal Patronage. The analytical parameters were DO, nitrite (NO 2 - ), nitrate (NO 3 - ), ammonia (NH 3 ), phosphate (PO 4 - ), and Total kjeldahl nitrogen (TKN) collected in three months (November 2020, January 2021, and March 2021). This research has presented the differences in water resource characters in three months and the positive impact of the COVID-19 lockdown on wastewater. The total nitrogen was highest in November 2020 when compared with that of in January and March 2021 because it was a ‘normal situation’ (no lockdown) in November. The student, officer, lecturer, and government visitors came to use the facilities of the university. The results of total kjeldahl nitrogen showed a high range during the working period. The effect of P was higher on the water bodies in November than January and March because in November was a normal situation (no lockdown). The N:P ratio showed different trends to the eutrophication phenomenon with nitrogen and phosphate. Therefore, a comparison between a situation with lockdown and no lockdown showed that the lockdown situation was environment friendly. Finally, the results also confirm an improvement in environmental quality, which happened when humans were absent, especially in coronavirus circumstances.